Epidemiology of Toscana Virus in Italy (2018-2020), a summary of available evidences. - Riccò, Matteo; Peruzzi, Simona (Acta Biomedica Atenei Parmensis, 2021)
Sir, Toscana Virus (TosV) is an arthropod-borne negative-stradend RNA virus belonging to the order of Bunyavirales, family of Phenuiviridae [1,2]. Originally isolated in 1971 in Tuscany, TosV is highly prevalent in countries bordering the northern shores of Mediterranean basin, mirroring the ecology of competent vectors (i.e. genera Phelebotomus and Sergentomyia) [1–6]. For instance, available reports from Italian regions of Piemonte, Emilia Romagna, Tuscany, Umbria, Puglia, Sicily and Sardinia have reported a prevalence for specific IgG antibodies ranging from 1.0% to 41.9% among healthy residents, and even more higher in some occupational groups (e.g. agricultural and forestry workers) [3–6]. While it is quite obvious that most of incident cases occur as pauci-symptomatic, the relatively high occurrence of IgM antibodies among patients complaining neurological symptoms (ranging between 4.7% to 27.2%) from the same areas suggests that a limited share of cases may develop a far more severe disorder [1,5]. Because of its potential epidemiological significance, since 2018 Italian National Health Service has included TosV neuroinvasive infections in the special surveillance for human arboviral infections, with periodic bulletins (https://www.epicentro.iss.it/arbovirosi/bollettini), whose content is subsequently summarized and discussed. Overall (Table 1), 182 cases of neuroinvasive TosV infections have been reported since 2018, with a case fatality ratio of 0.05%. Crude Incidence Rate was estimated in 0.101 cases per 100,000 (95% Confidence Interval [95%CI] 0.087-0.117), with an age-adjusted Incidence Rate (AIR) equals to 0.100 per 100,000, 95%CI 0.001-0.212. AIR were also heterogenous across the timeframe 2018-2020, being greater in 2018 (0.149 per 100,000), and then decreasing in the following years (0.093 and 0.060 for 2019 and 2020, respectively), while the majority of neuro-invasive TosV cases consistently occured during the months of August (38.5%), July (28.0%), and September (20.3%). Such a trend mirrored that of other arboviruses, and particularly West Nile Virus (WNV), that has been explained through the ecology of the vector [7,8]. Similarly to mosquitoes, intense warmth followed by precipitation deficits stimulate the replication of Phlebotomine, whose circulation is therefore particularly intense between July and September [9]. Unsurprisingly, 2018 was a record-breaking climate outlier in terms of summer temperatures, humidity, and lack of precipitation, that conversely were particularly intense during spring, and also Phlebotomine experienced an unprecedent thriving [1,9]. The role of the competent vector may also explain the increased risk for neuro-invasive TosV infections among males (70.3% of total cases) compared to females (Risk Ratio 2.498, 95%CI 1.817-3.434) (Table 2), as they are more commonly involved in outdoor activities (e.g. agriculture, forestry, and construction industries), particularly in the evening, at the peak of phlebotomine circulation [1,4]. On the contrary, despite the majority of incident cases occurred among and in subjects aged 0 to 39 years (38.5%), age groups 40 to 59 years-old and ≥ 60 years-old scored a risk for developing neuro-invasive infection similar to that of younger subjects.